Document classification in robotic process automation using artificial intelligence : a preliminary literature review - Ribeiro, Jorge (2020)
In recent decades, combined with technological evolution, numerous operational activities of companies are supported by information systems. Despite its advantages, countless routine tasks of the organizations are done manually. In recent years, robotic process automation (RPA) has emerged allowing to create automatic processes to deal with routine tasks. One typical feature of these systems is reading documents via optical character recognition (OCR) that are associated with the classification of documents. This paper aims to present a general study on the document classification process using OCR in RPA processes combined with the application of artificial intelligence. It was intended to carry out a survey of the state of the art of tools and approaches for the classification of documents using AI. Conclusions show that despite the challenges associated with the classification and categorization of documents, the applicability of AI techniques shows good results of accuracy to allow a better efficiency in the automation of RPA processes.